Lightning in the Andes and Mesoamerica : pre-columbian, colonial, and contemporary perspectives - Staller, John E. (Oxford University Press, 2013)
"Lightning has evoked a numinous response as well as powerful timeless references and symbols among ancient religions throughout the world. Thunder and lightning have also taken on various symbolic manifestations, some representing primary deities, as in the case of Zeus and Jupiter in the Greco/Roman tradition, and Thor in Norse myth. Similarly, lightning veneration played an important role to the ancient civilizations of Mesoamerica and Andean South America. Lightning veneration and the religious cults and their associated rituals represent to varying degrees a worship of nature and the forces that shape the natural world. The inter-relatedness of the cultural and natural environment is related to what may be called a widespread cultural perception of the natural world as sacred, a kind of mythic landscape. Comparative analysis of the Andes and Mesoamerica has been a recurring theme recently in part because two of the areas of "high civilization" in the Americas have much in common despite substantial ecological differences, and in part because there is some evidence, of varying quality, that some people had migrated from one area to the other. Lightning in the Andes and Mesoamerica is the first ever study to explore the symbolic elements surrounding lightning in their associated Pre-Columbian religious ideologies. Moreover, it extends its examination to contemporary culture to reveal how cultural perceptions of the sacred, their symbolic representations and ritual practices, and architectural representations in the landscape were conjoined in the ancient past. Ethnographic accounts and ethnohistoric documents provide insights through first-hand accounts that broaden our understanding of levels of syncretism since the European contact. The interdisciplinary research presented herein also provides a basis for tracing back Pre-Columbian manifestations of lightning its associated religious beliefs and ritual practices, as well as its mythological, symbolic, iconographic, and architectural representations to earlier civilizations. This unique study will be of great interest to scholars of Pre-Columbian South and Mesoamerica, and will stimulate future comparative studies by archaeologists and anthropologists."--Publisher's website